Structural Changes in the Medial Prefrontal Cortex and Anterior Cingulate Cortex of Dehydroepiandrosterone-Induced Wistar Rat Model of Polycystic Ovarian Syndrome - Enya Joseph Igbo; Ukwenya Okoliko; Imam Aminu; Aisha Kopada; Samson Olorunnado; Oluwole B. Akinola (Basic and Clinical Neuroscience, 2022)
Introduction: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder in women that is associated with an increased risk of infertility. This study aims to evaluate the neurobehavioral and neurochemical changes along with the associated changes in the medial prefrontal cortex (mPFC) and anterior cingulate cortex (ACC) of the dehydroepiandrosterone (DHEA)-induced PCOS model rats. Methods: A total of 12 female juvenile Wistar rats (30 to 50 g) about 22 to 44 days old were divided into 2 groups. The control group received sesame oil while the PCOS group received sesame oil plus DHEA. All treatment was done via daily subcutaneous injection for 21 days. Results: Subcutaneous DHEA-induced PCOS significantly depleted the line crossing and rearing frequency in the open field, along with the percentage of the time in the white box, line crossing, rearing, and peeping frequency in the black and white box, and the percentage of alternation in the Y-maze. PCOS significantly increased the immobility time, freezing period, and the percentage of time in the dark area in the forced swim test, open field test, and black and white box, respectively. The level of luteinizing hormone, follicle-stimulating hormone, malondialdehyde (MDA), reactive oxygen species (ROS), and interleukin-6 (IL-6) increased significantly, while norepinephrine depleted significantly with an obvious decrease in the brain-derived neurotrophic factor level in the PCOS model rats. PCOS rats exhibited cystic follicles in the ovaries and necrotic or degenerative like features in the hippocampal pyramidal cells. Conclusion: DHEA-induced PCOS results in anxiety and depressive behavior with structural alteration in rats, possibly through the elevation of MDA, ROS, and IL-6 levels, which also attributes to impaired emotional and executive functions in the mPFC and ACC.